Transformasi Pendidikan Menuju Kemandirian: Tinjauan Terhadap Praktik Baik Di SMA Negeri 3 Medan - Pretty Viorella Br Ginting; Liesna Andriany (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
Education in Indonesia is currently experiencing a significant paradigm shift, with an increasing focus on developing student independence. This article aims to investigate good practices that support educational transformation towards independence at SMA Negeri 3 Medan. The research method used is a qualitative approach, through in-depth interviews with teaching staff, classroom observations, and analysis of school documents. The research results show that there are a number of good practices at SMA Negeri 3 Medan that support student independence. Among them are the implementation of project-based learning which encourages students to take initiative and collaborate in solving problems, the use of technology as a learning tool that expands access to information, as well as the development of diverse extracurricular programs to facilitate the development of students' skills and interests outside the academic curriculum.These findings highlight the commitment of SMA Negeri 3 Medan in creating a learning environment that supports student independence. The implication of these findings is the importance of adopting liberating educational practices in other schools to increase learning effectiveness and prepare students to face complex future challenges.